Some Analyses of Scientific Research on Karakalpak Drama - Mambetova Mehribanu Kamalovna (Genius Journals, 2021)
In this article some of the scientific works related to dramaturgy in the science of Karakalpak literature is analyzed. In these works, the features related to the Karakalpak dramaturgy are shown, the theoretical views on the achievements and shortcomings of dramatic works are discussed. At the same time, the study of dramatic works in Karakalpak literature determines the degree of fulfillment of the requirements to its genre.
Keywords: Theater Critic; Dramaturgy; Comedy; Analysis